The Grasshopper Phenomenon: Studi Kasus Terhadap Profesional yang Sering Berpindah-pindah Pekerjaan - Teddi Prasetya Yuliawan; Fathul Himam (Faculty of Psychology, Universitas Gadjah Mada, 2007)
This study was directed to explore the grasshopper phenomenon, the professional workers who always moved from job to jobs. It was intended to understand and explain why individual professional changed his/her jobs repeatedly. Qualitative research approach with case study as the research strategy was implemented. Based on the story revealed from the respondents, this research explained that the grasshoppers individuals moved from one job to another because of motivational factors (such as financial, willing to learn, willing to search more challenging jobs, etc), basic need factors (self-fulfillment and a need to share), and supporting factors (such as networking, family support, etc). This study showed that being a grasshopper served as a tool for achieving the vision, that is to fulfill the two basic needs (self fulfillment and a need to share). Keywords: grasshopper, changing jobs, motivation, qualitative, case study